Settlement of First Collective Agreement: An Examination of the Canada Labour Code Amendment - Muthuchidambaram, S. (Relations industrielles / Industrial Relations, 1980)
The purpose of this paper is to examine the rationale behind and provisions of a recent amendment to the Canada Labour Code, where the parties negotiating a first collective agreement are unable to reach agreement and have met all the legal requirements precedent to a strike or lockout, the Minister of Labour may direct the Labour Relations Board to inquire into the dispute and if advisable settle the terms and conditions of the first collective agreement. That agreement will be binding on the parties and in force for one year. The reactions of the organized labour and employers to this amendment are also discussed.